Application of Competency-Based Discovery Learning Method in Islamic Cultural History Subjects to Learning Outcomes - Siregar, Balyan Oslerking; Siregar, Ahmad Sofyan; Rambe, Muhammad Asroi; Harahap, Azwar (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2024)
In this study, student learning outcomes were carried out by t-test on daily score by applying the Discovery Learning learning method. Then the core competencies that are expected from students are: able to practice a committed attitude in carrying out the mandate, as well as practicing innovative and creative behavior. Meanwhile, the basic competency that is expected is that students are able to appreciate that power is a mandate. The data on learning outcomes obtained in the field from students in class XI-3 at MAN Insan Cendekia South Tapanuli amounted to 20 people according to class attendance. The learning outcomes or scores obtained with a critical value of t with db 20 at a significance level of 5% are = -3, 984, 1% = 2.750. The t-calculated value obtained is = 3.5222. This means that the t-value (thit) is greater than the t-table value at the 5% significance level (tt) result: 1.729. THIT 3.5222), and in the significance level of the value of T-table 1% is still greater than the value of T-table 1%. The result of thit 3.5222 tt 2.860935 on t-table 1%. The t-calculation value based on the empirical evidence obtained, it can be concluded that the final result shows an increase in learning outcomes of grade XI-3 students when applying the discovery learning method and is acceptable with an average of 78.6.